The local-wisdom-based social capital for strengthening social resilience during the COVID-19 pandemic - Armaidy Armawi; Samuel Asdianto Limbongan (Masyarakat, Kebudayaan dan Politik, 2022)
Indonesia is renowned for its diversity and various local wisdom that live and flourish among the society. In preventing the spread of the COVID-19 pandemic especially when the Implementation of Restrictions on Community Activities (PPKM), the people of the Special Region of Yogyakarta employ an adaptive mechanism consisting of the manners and ways of behaving, acting, and serving in the social order. The local wisdom emerges from the knowledge of the local culture and establishes the wisdom of individuals, groups, and society. The objective is to describe the people’s condition, analyze the social capital and explain the social resilience of the people. The current study is a descriptive qualitative study and adopts a phenomenology to find meaning in society. The research location is in Sleman Regency, more precisely in Pogung Rejo, Sinduadi Village, Kapanewon Mlati. The process of collecting data by observation, interviews, and documentation. This study finds that society appears in social behavior and actions to strengthen social resilience during the COVID-19 pandemic. The study concludes that social resilience has been built in the people of the Special Region of Yogyakarta with its local wisdom has been embedded in the community.